PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN DI DESA SUNGAI BAKUNG - Sugiannor Sugiannor; Anjani Anjani (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
Development must have at least 3 targets: increasing the availability and expanding the distribution of goods; improving the standard of living, expanding economic and social choices. Sungai Bakung Village, Sungai Tabuk District in Banjar Regency, South Kalimantan, is one of the areas that is experiencing various development efforts in the infrastructure, economic, and social sectors. There are positive and negative perceptions from the community towards a Development. This study uses a qualitative method with a phenomenological approach where data is obtained through in-depth interviews with members of the village community in the Sungai Bakung Village area from residents from various different social strata, snowball sampling techniques, Basic Theory of Perception is the human process of understanding information either through the eyes to see, ears to hear, nose to smell, heart to feel which is channeled to the human mind and mind to become an understanding, The results of this study there are four perceptions of village development including from the perception of the development of physical facilities, economic development and socio-cultural development of the community, where each perception of these four developments has a positive value but needs improvement in this development process.